Religious Virtues Enhance and Align with the Ethical Principles of the U.S. Lawyers’ Model Rules of Professional Conduct - Murray, Peter E. (Advances in Social Sciences Research Journal, 2025)
The enduring ethical dilemma of whether to prioritize one’s duty to God or adherence to the rule of law remains a deeply philosophical and controversial issue. This study explores whether a U.S. lawyer’s modern ethical responsibilities outlined in the Model Rules of Professional Conduct (MRPC) stem primarily from Christian biblical interpretations, or the principles of other major world religions, Judaism, Islam, Hinduism, and Buddhism, or secular theories of social jurisprudence, which posit that ethical duties are grounded in societal expectations. A systematic review of published legal cases identified recurring themes, with the most alleged ethical breaches: as money, discrimination, communication, responsibilities, competence, anti-harassment, confidentiality, diligence, retaliation, supervision, compliance, and candor (P<0.05). Furthermore, the five major world religions had similar proportions of cases alleging ethical violations to each other (P>0.05). The close alignment between the World’s major religious virtues, secular jurisprudence, and MRPC ethical rules are likely due to the historical roots of law in religious traditions. This analysis has shown that lawyers should integrate their religious virtues, such as honesty, integrity and trustworthiness, whether derived from Christianity, Judaism, Islam, Hinduism, or Buddhism, into their professional ethical obligations, as these principles are inherently compatible with modern legal practice.